Homosexuality's Signalling Function in Job Candidate Screening: Why Gay Is (Mostly) OK - Philippe Sterkens; Axana Dalle; Joey Wuyts; Ines Pauwels; Hellen Durinck; Stijn Baert (Institute of Labor Economics (IZA), 2022)
To explain the mixed findings on hiring discrimination against homosexual applicants, we explore the perceptual drivers behind employers' evaluations of gay men and lesbian women. Therefore, we conduct an extensive vignette experiment among 404 genuine recruiters, for which we test systematically-selected perceptions theoretically associated with homosexual job candidates in earlier studies. We find causal evidence for distinct effects of sexual identities on candidate perceptions and interview probabilities. In particular, interview probabilities are positively (negatively) associated with the perception of lesbian women (gay men) as being more (less) pleasant to work with compared to heterosexual candidates. In addition, interview chances are negatively associated with the perception of gay men and lesbian women as being more outspoken. Furthermore, our data align well with the idea of a concentrated discrimination account, whereby a minority of employers who privately hold negative attitudes towards homosexual individuals are responsible for most instances of hiring discrimination.
Keywords: C91; J15; J71; 330; homosexuality; signalling; statistical discrimination; taste-based discrimination; hiring experiment